Optimization of Parameters of Two-Beam Laser Twelding of Quartz Raw Materials - V. A. Emelyanov; E. B. Shershnev; Y. V. Nikitjuk; S. I. Sokolov; I. Y. Aushev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
In the work, with the help of numerical simulation, the values of technological parameters are established, which provide effective two-beam laser cleaning of quartz raw materials. The optimization of two-beam laser cleaning of quartz raw materials was performed using the MOGA genetic algorithm in the ANSYS Work-bench program. Using the face-centered version of the central compositional plan of the experiment, a regression model of two-beam cleaning of quartz raw materials was obtained. The power density of a laser with the wavelength of 10.6 μm, the power density of a laser with the wavelength of 1.06 μm, the radius of a quartz particle, the radius of an impurity particle, and the processing time were used as variable factors. The maximum temperatures of quartz particles with impurities and quartz particles without impurities were used as responses. The regression model was tested. The results obtained allow us to conclude that there is a necessary correspondence between the regression model and the finite element analysis data. An assessment of the influence of processing parameters on the maximum values of the temperature of quartz particles was made. Optimization of two-beam laser cleaning of quartz raw materials was carried out according to the criterion of minimum processing time when reaching the maximum temperatures of quartz particles with an admixture of the melting temperature and limiting the maximum temperatures of quartz particles without an admixture to values below the melting temperature. Optimization was performed for two combinations of quartz and impurity particle sizes. The parameters obtained as a result of optimization and the parameters obtained as a result of finite element modeling are compared. The maximum relative error of the results obtained using the MOGA algorithm did not exceed 2.5 % when determining the maximum temperatures. As a result of the simulation, processing parameters have been established, the use of which will provide an increase in the productivity of two-beam purification of quartz raw materials.